Pelatihan Mendeley Sebagai Manajemen Referensi bagi Mahasiswa - Ayu Rakhma Wuryandini; Lukman Pakaya; Kadek Hartana (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2021)
The objectives of this service activity are: 1) To increase the knowledge of the participants, namely students, the importance of the Mendeley application as a reference management of library resources in research. 2) To improve the ability of the participants, namely students, to be able to operate the Mendeley application properly and correctly. The stages of work carried out by the implementing team in this community service program are providing training and providing assistance in managing reference sources of libraries in scientific works and being able to operate the Mendeley application properly and correctly. This activity was attended by 7th (seven) students of the Faculty of Economics, majoring in Accounting, UNG, who were preparing proposals and theses. The expected result of this service program is that it can improve the skills of students as young researchers to manage references to library sources or citations so that the writings in scientific works are presented properly and correctly in accordance with the procedures for writing scientific papers that are applied.